Plasma-catalytic NOx production in a three-level coupled rotating electrodes air plasma combined with nano-sized TiO2. (10th December 2021) - Lei, Xinyu; Cheng, He; Nie, LanLan; Xian, YuBin; Lu, Xinpei
Abstract: A novel three-level coupled rotating electrodes air plasma with nano-sized TiO2 photocatalysts is developed for plasma-catalytic NO x production. The effects of plasma catalysis on NO x production with different air flow rates, different N2 fractions and different humidity levels are evaluated. Final results show the exceptional synergistic effect between TiO2 and three-level coupled rotating electrodes air plasma significantly increases the NO x concentration by 68.32% (from 4952 to 8335 ppm) and reduces the energy cost by 40.55% (from 2.91 to 1.73 MJ mol −1 ) at an air flow rate of 12 l min −1 and relative humidity level of 12%, which beats the ideal thermodynamic energy limit ∼2.5 MJ mol −1 for the thermal gas-phase process. A possible mechanism for enhanced NO x production with TiO2 is discussed: Highly energetic electrons in plasma contribute to the formations of the electron–hole pairs and oxygen vacancy (Vo ) on the TiO2 catalyst surface, which may facilitate the dissociative adsorption of O2 molecules to form superoxide radical groups (like O2 − ), and H2 O molecules to form surface hydroxyl groups (like OH · ), and thus, improving energy efficiency.